Prevalence and Determinants of Smoking among Healthcare Professionals in Hyderabad - Zamir Hussain Tunio, Rizwan Ali Jhatiyal, Shehla Channa, Omar Parvez Khan, Asadullah Makhdoom, Jahanzeb Hasan Khaskheli, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the prevalence of cigarette smoking in doctors, nurses and paramedics and to study different aspects related with it. Study Design: Cross-sectional survey Place and Duration of Study: Liaquat University Hospital Jamshoro/Hyderabad from 1st March 2021 to 30th April 2021. Methodology: Seven hundred health care professionals and staff including consultants, postgraduate residents, house officers, medical officers & paramedics, nurses, dispensers, ward boys and sweepers. A self-made questionnaire was used to collect information from the participants. The first part of questionnaire has demographics followed by smoking status and certain set of questions regarding smoking habits from smokers. All reasons to fail to quit smoking and factors influencing to quit smoking were also analysed. Results: The mean age of all participants was 38.15±8.85. 85% of the participants were males and 15% were females. The prevalence of smoking in health care professionals was 24.17%. The reasons for failure to quit smoking were lack of will power in 35.38% participants, friends smoking circle in 27.69%, withdrawal symptoms after quitting in 26.15% and smoker family member in 10.76%. The factors influencing to quit smoking in ex-Smokers were will power in 20%, fear of Health hazards in 16.92%, insistence of partner 12.3%, friends in 10.7%, bad effect on patients 9.23%, kids 7.69% and multiple factors in 23.07% participants were reported. Conclusion: The smoking prevalence was 24.17% among our hospital workers. Friend circle was the leading influencing factor to begin smoking and lack of will power was main hurdle to quit smoking habit. Keywords: Smoking, Prevalence, Health care professionals, Smoking attitudes, Pakistan